Party politics and economic reform in Africa's democracies - Pitcher, M. Anne. (New York : Cambridge University Press, 2012)
"In Party Politics and Economic Reform in Africa's Democracies, M. Anne Pitcher offers an engaging new theory to explain the different trajectories of private sector development across contemporary Africa. Pitcher argues that the outcomes of economic reforms depend not only on the kinds of institutional arrangements adopted by states in order to create or expand their private sectors but also on the nature of party system competition and the quality of democracy in particular countries. To illustrate her claim, Pitcher draws on several original datasets covering twenty-seven countries in Africa and detailed case studies of the privatization process in Zambia, Mozambique, and South Africa. This study underscores the importance of formal institutions and political context to the design and outcome of economic policies in developing countries."--Provided by publisher
Understanding institutional development in Africa: an introduction -- From motivational to imperative commitment: variation and convergence of private sector institutions across Africa -- The impact of party politics and democratic quality on economic restructuring -- Party fragmentation and ad hoc privatization in a limited democracy: Zambia -- Stable parties, limited democracy and partisan privatization: Mozambique -- Stable parties, liberal democracy and strategic compromise: South Africa -- Conclusion: rules, politics, and discretion.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Africa -- Economic policy; Political parties -- Africa; Democratization -- Africa; Afrique -- Politique économique.; Démocratisation -- Afrique; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- General; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Structural Adjustment; POLITICAL SCIENCE -- Public Policy -- Economic Policy; Réformes économiques.; Démocratisation.; Privatisation; Partis politiques; Afrique; Democratization; Economic policy; Political parties; Africa